2020
DOI: 10.3389/fphys.2020.606889
|View full text |Cite
|
Sign up to set email alerts
|

Sorting Sox: Diverse Roles for Sox Transcription Factors During Neural Crest and Craniofacial Development

Abstract: Sox transcription factors play many diverse roles during development, including regulating stem cell states, directing differentiation, and influencing the local chromatin landscape. Of the twenty vertebrate Sox factors, several play critical roles in the development the neural crest, a key vertebrate innovation, and the subsequent formation of neural crest-derived structures, including the craniofacial complex. Herein, we review the specific roles for individual Sox factors during neural crest cell formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 189 publications
(296 reference statements)
1
44
0
Order By: Relevance
“…This may indicate a possible interaction of SOX3 with the formation of cleft affected tissue. Information about the role of SOX3 involvement in the development of cleft lip is limited, but together with other SOX genes it contributes to the correct formation of facial structures during embryonic development [ 35 ]. SOX3 belongs to SoxB1 protein family together with SOX2 and SOX1, which have some overlap in function, and mostly regulate the development and proliferation of neural and sensory tissues, but also affect the developing craniofacial region [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate a possible interaction of SOX3 with the formation of cleft affected tissue. Information about the role of SOX3 involvement in the development of cleft lip is limited, but together with other SOX genes it contributes to the correct formation of facial structures during embryonic development [ 35 ]. SOX3 belongs to SoxB1 protein family together with SOX2 and SOX1, which have some overlap in function, and mostly regulate the development and proliferation of neural and sensory tissues, but also affect the developing craniofacial region [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, within the context of embryonic development, the SOXF (7, -17 and 18) transcription factors have been shown to act mainly as transcriptional activators (Chew and Gallo, 2009). Unlike the SOXB2 transcription factors (SOX21 and SOX14) that possess a repression domain, SOXF proteins have a transactivating domain (Schock and LaBonne, 2020; Uchikawa et al, 1999). Similar to SOX18 and SOX17 (Corada et al, 2013; François et al, 2008; Hosking et al, 2004), SOX7 has primarily been reported to positively regulate gene transcription (Chiang et al, 2017; Costa et al, 2012; Futaki et al, 2004; Kim et al, 2016; Murakami et al, 2004; Niimi et al, 2004; Sacilotto et al, 2013), although there have been a handful of reports of SOX7 acting to repress transcription via the sequestration of activators through direct protein-protein interaction (Fan et al, 2018; Guo et al, 2008; Lilly et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Positive cis-regulatory elements, also known as enhancers, serve as important "switches" within GRN modules by integrating inputs/binding of upstream factors in order to coordinate output/expression of downstream targets. SOX10E1 and SOX10E2 enhancers, situated 1 kb downstream of the coding region for NC master regulator Sox10 (Kelsh, 2006;Sauka-Spengler and Bronner-Fraser, 2008;Schock and LaBonne, 2020) have been shown to control the expression of Sox10 in the chicken embryo (Betancur et al, 2010). Both enhancers demonstrated distinct spatiotemporal activity, where SOX10E2 alone was active in early delaminating cNC cells.…”
Section: Cis-regulatory Elements Unify Nc Gene Modulesmentioning
confidence: 99%
“…Broadly-speaking, Wnt, Fgf, and Bmp signals at the neural plate border activate expression of genes from the Msx, Pax, and Zic families during NC induction (Ikeya et al, 1997;LaBonne and Bronner-Fraser, 1998;Monsoro-Burq et al, 2003Lewis et al, 2004;Schumacher et al, 2011). Pax3 and Zic1 activate expression of bona fide NC factors, such as Snai1 and FoxD3, thus driving the onset of NC specification defined by the expression of Tfap2, Id, Myc, Myb, SoxE, and Ets gene family members (Luo et al, 2003;Sato et al, 2005;Hong and Saint-Jeannet, 2007;Sauka-Spengler et al, 2007;Milet et al, 2013;Schock and LaBonne, 2020). The persisting expression of these TFs, as well as the downstream activation of cadherins, integrins, signaling receptors and metalloproteases, subsequently lead to epithelial-to-mesenchymal transition (EMT) and delamination of NC cells from the dorsal neural tube.…”
Section: Introductionmentioning
confidence: 99%